Schematic outline of Brazilian soils - Camargo, Marcelo N.; Bennema, Jakob (Pesquisa Agropecuaria Brasileira, 2024)
Information on characteristics and geographical distribution of soils in Brazil is too restricted to provide the basis for a reasonably precise overall outline even of a schematic or generalized type, as is the case of the present approach. The availability and detail of information on soils is heterogeneous and scattered, and lacking for certain zones of Brazil. To overcome provisionally this deficiency, information has been assembled, and an attempt made at the composition of an outline on the soils of the country. Such a draft, which has to be schematic, has been developed by means of compilation, generalization, extrapolation and inference according to known correlations prevailing for the local environment. The appraisal from the pedological and geographical viewpoint has led to the setting up of twenty general soil associations, which are essentially distinguished by the predominant, and whenever possible, exclusive component classes of soils. To place the tentative definition of each association on a more objective basis, the fundamental classes of soils which form the associations have been briefly described. The nomenclature used for the different soils refers basically to the American soil classification system. The tentative descriptions of the twenty associations of the draft comprise only the specification of the predominant, subdominant and ocasionally occuring soils, as the components of each association.